If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(x + 3) = x * x + -10 Reorder the terms: (2 + x)(x + 3) = x * x + -10 Reorder the terms: (2 + x)(3 + x) = x * x + -10 Multiply (2 + x) * (3 + x) (2(3 + x) + x(3 + x)) = x * x + -10 ((3 * 2 + x * 2) + x(3 + x)) = x * x + -10 ((6 + 2x) + x(3 + x)) = x * x + -10 (6 + 2x + (3 * x + x * x)) = x * x + -10 (6 + 2x + (3x + x2)) = x * x + -10 Combine like terms: 2x + 3x = 5x (6 + 5x + x2) = x * x + -10 Multiply x * x 6 + 5x + x2 = x2 + -10 Reorder the terms: 6 + 5x + x2 = -10 + x2 Add '-1x2' to each side of the equation. 6 + 5x + x2 + -1x2 = -10 + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 6 + 5x + 0 = -10 + x2 + -1x2 6 + 5x = -10 + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 6 + 5x = -10 + 0 6 + 5x = -10 Solving 6 + 5x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5x = -10 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = -10 + -6 5x = -10 + -6 Combine like terms: -10 + -6 = -16 5x = -16 Divide each side by '5'. x = -3.2 Simplifying x = -3.2
| 8+4x=5y | | x-17=2x | | x^7+7x^6=0 | | 20x^2-17x-24= | | 2y-(-3-5y)=(y+2)+37 | | (8x+9)+(-6x-1)= | | -32x-4=44 | | 6-9p+11-2p+p-8+r= | | -11-5v=1-3v | | f(x)=9.5x-2 | | 2x+y=36.5 | | 3x+9=99 | | (-2+4)+(x-11)= | | 2w(-8w-3)= | | -2(-6n+7)+5n=-150 | | 12x-12y=4 | | 4.6x+56.4=12.9-9.9x | | 3+3x=15-3x | | 10+0.10x=.35x | | 90+15x=125+12x | | 45=x+0.13x+0.15x | | -5(4y+5)-11=-8(y+7)+4y | | 3k+5m-2mk+4+4mk-4k= | | 7+15x=3(5x+3) | | 5(2x+12)=18 | | 3.5=2.2 | | 7r-2+5r=7r+6-4R | | -(20-3m)=8(m+5) | | 3(g-7)=60 | | 4x+3-8x-12=-25 | | 1(20-3m)=8(m+5) | | 10x+1=-5x-24 |